1985
DOI: 10.1080/17450398509426962
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Vitamin-A-Bedarf des wachsenden Schweines

Abstract: In 9 experiments the vitamin A content of the livers of 64 newborn (still births and deaths up to 48 h p.p.) and 69 weaned piglets, 122 growers and 110 fattening pigs was investigated after slaughtering or autopsy. Liver samples were taken from 78 growers by means of biopsy after latarotomy. A fluorometric analysis of the plasma vitamin A level was made. At the time of birth the vitamin A content of the piglet livers was less than 100 IU/g and did not show any differences between the experiments. At the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…On the other hand, the highest level,about 100 mg/100 g liver, was also reported by Hirvi et al (1992) found in samples taken from a practical slaughter line. Hennig et al (1985) reported a highly significant linear relationship between vitamin A content in feed and vitamin A content in the liver. In the present study, a similar relationship was noticed, but the linearity was not tested.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the highest level,about 100 mg/100 g liver, was also reported by Hirvi et al (1992) found in samples taken from a practical slaughter line. Hennig et al (1985) reported a highly significant linear relationship between vitamin A content in feed and vitamin A content in the liver. In the present study, a similar relationship was noticed, but the linearity was not tested.…”
Section: Resultsmentioning
confidence: 99%